Gut microbiota: a newly identified environmental factor in systemic lupus erythematosus - Yao, Kaijin; Xie, Yina; Wang, Jiali; Lin, Yongda; Chen, Xiutian; Zhou, Tianbiao (Frontiers in Immunology, 2023)
Systemic lupus erythematosus (SLE) is a chronic autoimmune disease that predominantly affects women of childbearing age and is characterized by the damage to multiple target organs. The pathogenesis of SLE is complex, and its etiology mainly involves genetic and environmental factors. At present, there is still a lack of effective means to cure SLE. In recent years, growing evidence has shown that gut microbiota, as an environmental factor, triggers autoimmunity through potential mechanisms including translocation and molecular mimicry, leads to immune dysregulation, and contributes to the development of SLE. Dietary intervention, drug therapy, probiotics supplement, fecal microbiome transplantation and other ways to modulate gut microbiota appear to be a potential treatment for SLE. In this review, the dysbiosis of gut microbiota in SLE, potential mechanisms linking gut microbiota and SLE, and immune dysregulation associated with gut microbiota in SLE are summarized.